Dynamic Protease Activation on a Multimeric Synthetic Protein Scaffold via Adaptable DNA‐Based Recruitment Domains. (8th April 2021) - Mashima, Tsuyoshi; Rosier, Bas J. H. M.; Oohora, Koji; de Greef, Tom F. A.; Hayashi, Takashi; Brunsveld, Luc
Abstract: Hexameric hemoprotein (HTHP) is employed as a scaffold protein for the supramolecular assembly and activation of the apoptotic signalling enzyme caspase‐9, using short DNA elements as modular recruitment domains. Caspase‐9 assembly and activation on the HTHP platform due to enhanced proximity is followed by combinatorial inhibition at high scaffold concentrations. The DNA recruitment domains allow for reversible switching of the caspase‐9 assembly and activity state using short modulatory DNA strands. Tuning of the recruitment domain affinity allows for generating kinetically trapped active enzyme complexes, as well as for dynamic repositioning of caspases over scaffold populations and inhibition using monovalent sink platforms. The conceptual combination of a highly structured multivalent protein platform with modular DNA recruitment domains provides emergent biomimicry properties with advanced levels of control over protein assembly. Abstract : A hexameric protein recruitment platform allows controlled assembly and activation of caspase‐9 enzymes using short DNA sequences as modular recruitment domains. Simple molecular tuning of the DNA recruitment domains enables reversible switching or kinetic inhibition of the proximity‐induced enzyme activation.